2021
DOI: 10.3390/ijerph182111702
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among the Younger Generation in Japan

Abstract: Japan has vaccinated its older population; a mass vaccination program for younger citizens is underway. Accordingly, this study investigated vaccine hesitancy among younger Japanese citizens. We used online panel survey data from the Hiroshima Institute of Health Economics Research of Hiroshima University and applied probit regression models. Our study found that vaccine hesitancy among younger people was significantly higher than among older people. Moreover, vaccine hesitancy was significantly higher among y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
5
32
1
Order By: Relevance
“…However, removing from the analyses participants who reported intention to vaccinate, we found that participants younger than 49 had higher odds of hesitancy than individuals between 50 and 64 years old. The literature is in agreement with higher hesitancy for younger age groups [2][3][4]6,[8][9][10]13,14,[16][17][18]20,22,24,30,33,36,37,40,46]. We categorised age using the same age groups used by the official Portuguese reports for our analysis, which indicate a similar trend [46].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…However, removing from the analyses participants who reported intention to vaccinate, we found that participants younger than 49 had higher odds of hesitancy than individuals between 50 and 64 years old. The literature is in agreement with higher hesitancy for younger age groups [2][3][4]6,[8][9][10]13,14,[16][17][18]20,22,24,30,33,36,37,40,46]. We categorised age using the same age groups used by the official Portuguese reports for our analysis, which indicate a similar trend [46].…”
Section: Discussionsupporting
confidence: 58%
“…Health status and having diseases were other important factors in vaccine hesitancy. This study found that participants who perceived their health status as reasonable and had two or more diseases had lower odds of hesitancy than participants with a good health perception and no diseases [8,18,34,36,40,46]. Additionally, we found that participants who felt negative emotions some days had lower odds of hesitancy.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In Japan, the proportion of non-regular employees is high, especially among women and young people [27]. Household income has been reported to be a factor in vaccine hesitancy [28]. Non-regular employees are concerned not only about side effects of the vaccine, but also about the possible loss of income due to the difficulty of working as a result of side effects.…”
Section: Compensation For Non-regular Employeesmentioning
confidence: 99%